Turning Vietnam's COVID-19 Success into Economic Recovery: A Job-Focused Analysis of Individual Assessments on Their Finance and the Economy - Hai-Anh H. Dang; Long T. Giang (Global Labor Organization (GLO), 2020)
The COVID-19 pandemic has resulted in income and employment loss in many countries around the world. Yet, hardly any formal study exists on household finance and future economic expectations in poorer countries. To fill in this gap, we implemented and analyzed a web-based rapid assessment survey immediately after the removal of lockdown measures in Vietnam, a lower-middle-income country that has received widespread recognition for its successful fight against the pandemic. We find that having a job is strongly and positively associated with better finance and more income and savings, as well as more optimism about the resilience of the economy. Further disaggregating employment into different types of jobs such as self-employment and jobs with permanent and short-term contracts, we find those with permanent job contracts to be more strongly associated with better assessments and fewer job worries. Individuals with good health and higher educational levels also have more positive evaluations for their current and future finance. These findings are relevant for post-outbreak economic policies, especially regarding the labor market in a developing country context.
Keywords: I1; I3; J01; J08; O1; 330; COVID-19; recession; labor market; wage work; household finance; Vietnam